Design of Novel MSK Architectures Using R-F Bit - Sonmez, Mehmet; Akbal, Ayhan (Kaunas Univ Technology, 2016)
In this paper, we present two novel reformulations (1) and (20) for MSK (Minimum Shift Keying) modulation technique. By using these novel reformulations, we find an additional switching bit, referred to as R-F bit, and propose a novel MSK architecture. Compared to known prior MSK architectures, our architecture offers significant advantages with respect to power consumption and hardware efficiency. Additionally, a pre-computation technique is used to reduce ram bit utilization (RBU) of the proposed modulator. Considering the whole modulation procedure, this approach reduces the RBU of the proposed architecture by 75%. The experimental results show that our architecture is very suitable for MSK modulation.
Keywords: R-F bit; pre-computation; MSK; FPGA; NCO